(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article states that achievement of the desired level of financial safety of joint stock companies requires increase of their investment attractiveness on the basis of growth of the dominant development of corporate structures. The basic approaches of scientists to understanding, classification and evaluation of risks, as well as their role in the financial security of joint stock companies are determined. It is proved that the current practice of risk assessment as an instrument of financial security management of joint stock companies requires improvement in the part of the assessment of the influence of risk factors on indicators of the financial security of corporate structures. To this end, the author examines the main characteristics of the risks involved in providing financial security to business structures. The main methodological approaches to enterprise risk assessment are systematized. The author’s approach to risk assessment is proposed by applying normative and fundamental methods of their estimation in symbiosis. Such a scientific and methodological approach is based on such an assumption that the possibility of obtaining losses by joint stock companies is generated by the threats of their activities, and the probability of obtaining positive benefits - their dominant. The scope of the risks, which determine the increase or decrease of the financial security of joint stock companies, is identified, and the constraints and risk of financial security of corporate structures are identified. The optimal values of the indicators of the financial safety of joint stock companies in Ukraine are proposed to be determined on the basis of expert assessments. A source of risk of financial safety of joint stock companies is identified with the help of an assessment of the impact on the indicators of the financial state of the factors that make up them. The algorithm of the derivation of the relationship between factors and the resultant indicator of the financial security of joint stock companies is developed.